Technology and delivery of justice - Ali Mohamed, Ashgar Ali (CLJ Publication, 2020)
The main business of the Judiciary is to interpret and enforce the laws enacted by the Legislature including the Federal Constitution, State Constitutions and any other source of law recognised by the legal system. The courts perform their task in accordance with the oath taken by judges to uphold the Constitution and the enacted laws. ‘The courts are the final arbiter between the individual and the State and between individuals inter se, and in performing their constitutional role, they must of necessity and strictly be in accordance with the Constitution and the law be the ultimate bulwark against unconstitutional legislation or excesses in administrative action.’ If that role of the Judiciary is appreciated, then it will be seen that the courts have a duty to perform in accordance with the oath taken by judges to uphold the Constitution and to act within the provisions of and in accordance with the law.’3A judge must ‘maintain the highest traditions of judicial rectitude, independence and impartiality.’4 He should have an open mind and should not be biased against the person whom the action is sought to be taken nor should he be someone who has prejudged the issue.